Analytical characterization of ancient mortars from the archaeological roman site of Pisões (Beja, Portugal). (20th April 2019) - Borsoi, G.; Santos Silva, A.; Menezes, P.; Candeias, A.; Mirão, J.
Highlights: The Pisões archaeological site: an ancient roman construction in the Iberian Peninsula. Microstructural and chemical-mineralogical characterization of ancient mortars. Good state of conservation, strength and durability of these mortars. Careful selection of the materials and skilled craftsmanship. Abstract: The analytical characterization of mortar samples from the roman archaeological site of Pisões, located in Southern Portugal, were carried out by means of X-ray diffractometry (XRD), thermogravimetry (TGA-DTA), optical and electron scanning microscopy (SEM-EDS), potentiometry and combustion analysis. The Pisões archaeological complex includes a villa rustica, characterized by well-preserved mosaics and thermal baths, as well as a mill and a mausoleum. Countryside villae epitomized the Romanization of the Iberian Peninsula for over six centuries (2nd century BCE–4th century CE). Nevertheless, most of the Roman villae identified in Portugal have not yet been systematically explored and studied. This study provides valuable data on the construction materials and techniques used in Roman times in the Iberian Peninsula. The careful selection of raw materials and the use of natural and artificial pozzolanic materials can explain the favourable state of conservation, mechanical strength and long-term durability of these mortars.